The effectiveness of training in Sarawak Energy Berhad: Competency Training Division / Nuur Ain Nadhirah Brahim - Brahim, Nuur Ain Nadhirah (University Technology MARA Sarawak, 2014)
The blue wave represents the mighty rivers of Sarawak which is the source of hydropower, whereas the green wave symbolizes the forest and the natural environment, drawing energy from the sun. Together the waves represent clean and renewable energy, sustaining life and growth for Sarawak and its people. While, the use of lower case letters in their name signals the openness and humility towards their customers and their community.